2020
DOI: 10.1016/j.matt.2020.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate Clusters: Sub-nanometer Building Blocks for Construction of Advanced Materials

Abstract: Cluster-assembled materials based on polyoxometalates (POMs) process unprecedented structural tunability and polymer-like behaviors because of the sub-nanometer-sized building blocks and their non-covalent linkage. Through the whole journey in their development, exquisite POM cluster assemblies with advanced functions spring up, and the control over their nanostructures tends to be more precise and reach their nature at molecular level. In this paper, recent progress in cluster-assembled materials based on POM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 140 publications
(131 reference statements)
4
73
0
Order By: Relevance
“…Besides the aforementioned ionic additives for block copolymers, polyoxometalates (POMs), the nanosized, anionic molecularly defined clusters of metal oxides have attracted much attention for their abilities in inducing phase transitions as multi‐charged ions and fabricating functional hybrid polymer materials as typical inorganic moieties. [ 23–36 ] Recently, their high proton conductivity, thermal stability and water‐retention capability have been appealing for nanostructured proton‐conducting polymer hybrid electrolytes. [ 37–40 ] For example, Guiver et al.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the aforementioned ionic additives for block copolymers, polyoxometalates (POMs), the nanosized, anionic molecularly defined clusters of metal oxides have attracted much attention for their abilities in inducing phase transitions as multi‐charged ions and fabricating functional hybrid polymer materials as typical inorganic moieties. [ 23–36 ] Recently, their high proton conductivity, thermal stability and water‐retention capability have been appealing for nanostructured proton‐conducting polymer hybrid electrolytes. [ 37–40 ] For example, Guiver et al.…”
Section: Methodsmentioning
confidence: 99%
“…[ 8–12 ] In addition to the latest developments in atomically precise ultrasmall particles (mainly limited to below 3 nm), there is also a need to realize their programmable structure (or self‐assembly) into functional materials with a high level of hierarchy, complexity, and accuracy, up to the micro‐ or even macroscale. [ 13–20 ] This multiscale assembly of atomically precise ultrasmall particles provides a reliable platform for the bottom‐up construction of artificial functional materials across all scales, which is an intrinsic requirement for manifesting universal functionality in nature and life. [ 21–23 ] In addition, it also enables the assembly to have imposed stability, collective (and often synergistic) functionality, and expected processability, thereby increasing their acceptance in various fields of practical applications.…”
Section: Figurementioning
confidence: 99%
“…In this context, with continuous progress, several feasible strategies have been deployed: 1) using various directing agents to perform long‐distance self‐assembly/crystallization of atomically precise ultrasmall particles through weak forces (e.g., dipolar, van der Waals, and supramolecular interactions), where the surface chemistry and the specific colloidal environment of the atomically precise ultrasmall particles are keys to the success of this method; [ 13,14,24–26 ] 2) introducing predesigned organic linkers to coordinate with atomically precise ultrasmall particles to construct periodically extended solids, which usually have well‐defined geometry and connectivity; [ 27–29 ] and 3) using a neat polymerization of atomically precise ultrasmall particles through effective homogeneous or heterogeneous metallophilic interactions, which are usually observed in single crystals. [ 30,31 ] These obtained atomically precise ultrasmall particles based micro‐/macroscale materials have shown impressive performance in optical, electronic, and catalytic applications.…”
Section: Figurementioning
confidence: 99%
“…Polyoxometalate complexes have a fixed size of the order of 3–5 nm [ 16 , 17 , 18 , 19 , 20 , 21 ]. Today, the class of polyoxometalate complexes is being actively studied, and structures of various compositions, shapes, and sizes were previously obtained [ 22 , 23 , 24 , 25 , 26 ]. Research found that polyoxometalates containing molybdenum are formed as a result of the self-assembly process from the initial building blocks Mo 1 , Mo 2 , Mo 8 , etc.…”
Section: Introductionmentioning
confidence: 99%